Expression of GD3 ganglioside by developing rat cerebellar Purkinje cells in situ. - Reynolds,R; Wilkin,GP (J Neurosci Res, 1988)
GD3 is a major ganglioside of the immature vertebrate CNS, and its expression is suggested to be characteristic of immature neuroectodermal cells. Using immunocytochemistry on cryostat sections of developing rat cerebellum with a monoclonal antibody specific for GD3, we have found that GD3 begins to be expressed on the plasma membrane of Purkinje cell bodies and dendrites beginning at postnatal day 7. Staining became brighter as the dendritic tree of the cells enlarged. As the Purkinje cells began to mature in different folia, they became GD3+, until by 15 days postnatal all Purkinje cells were GD3+. Positive staining of the dendritic tree was still present in the adult cerebellum. Using a monoclonal antibody 7-8D2, which recognizes cerebellar granule cells and their axons (the parallel fibres), and polyclonal antibodies against a synaptic vesicle component synaptophysin, double-immunofluorescence staining together with anti-GD3 antibodies suggested that the appearance of GD3 immunoreactivity did not correlate either with the ingrowth of parallel fibres or the presence of their synapses on Purkinje cell dendrites. However, comparison with earlier morphological studies showed that the appearance of GD3 immunoreactivity correlated well with the formation of climbing fibre synapses on Purkinje cell dendrites and the onset of the rapid expansion of the dendritic tree. These results are in keeping with the idea that elevated GD3 concentrations are found in certain cell types during periods of rapid growth or high metabolic activity but also show that this is not only restricted to immature cells.